The Regional Government Policy towards the Development of Sports Facilities and Infrastructure in Ternate City, North Maluku Province - Abas, Rudi; Sugiharto, Sugiharto; Sulaiman, Sulaiman (Study Program Education and Sports, Postgraduate Universitas Negeri Semarang, 2019)
The study aims to analyze and study the regional government's authority towards the sports facilities and infrastructure in Ternate City, North Maluku that covers implementation, planning in equipping, management and the utilization of sports facilities and infrastructure in Ternate City. It used a qualitative approach with ethnography design type of critical ethnography. The subject of the study was regional development, research, and development planning board (Bappelitbangda), Youth and Sports Office (Dispora), 8 districts, National Sports Community of Indonesia (KONI), Central Bureau of Statistics (BPS) and Regional Legislative Assembly (DPRD). The results of study are the authority of regional government towards the sport facilities and infrastructure is arranged under the regional regulation of Ternate City Number 39 of 2012 related to the Long-term Development Plan (RPJP), the implementation of the authority is not running well, the planning in equipping the facilities and infrastructure in Ternate City through Multi-Stakeholder Consultation Forum for Development Planning (Musrenbang) in sub-district, district, and city Management of sport facilities and infrastructure under the authorities of regional government that allocated through Provincial or District Government Budget (APBD) under the responsibility of Dispora, Facilities and infrastructure could be used by the society of Ternate city and the athletes. It can be concluded that the authority of regional government is arranged by Mayor, Dispora, District, Sub-district and society, the implementation of the authority is not running well yet, the planning in equipping is through Musrenbang, the management of facilities and infrastructure is partly managed by regional government, the society can utilized the sports facilities and infrastructure.